A New Species of Nervilia Gaud. (Orchidaceae) from Garhwal Himalaya (India) - Nageswara Rao, A. (Indian Forester, 1992)
A new species of Nervilia Gaud. Nervilia gleadowii Nageswara Rao from Tehri Garhwal, U.P. is described. This species is allied to Nervilia scottii/I> (Rchb.f.) Schltr. but differs in having the flowers erect and close together, the bracts erect and the lip with glabrous disc and oblong- elliptic midlobe. The specific epithet is named after Mr. F. Gleadow who collected the plant for the first time from Tehri Garwal in 1900.